Reward management - Rose, Michael 1953- (Kogan Page, 2014)
"Reward Management is a practical guide to understanding and implementing really effective reward strategies in your organization. Tailored to the needs of practitioners it uses a combination of practical tools, scenarios and case studies to cover areas including pay grades and structure, job evaluation, pay reviews, bonus plans, non-cash reward, benefits, tax issues and much more. Aligning reward with the strategic objectives of the organization it will equip you with the skills you need to plan, implement and assess a reward strategy in any type of organization"--
Keywords: BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Compensation management; Employee motivation; Incentives in industry; Wirtschaft; Compensation management -- Case studies; Incentives in industry -- Case studies; Employee motivation -- Case studies; Fallstudiensammlung